1971
DOI: 10.1136/gut.12.11.922
|View full text |Cite
|
Sign up to set email alerts
|

Observations on liver regeneration after right hepatic lobectomy

Abstract: SUMMARY Restoration of liver mass has been studied in five patients after right hepatic lobectomy. The operation effects an approximate 50 % resection of liver substance. Postmortem observations, measurements of the weight of liver resected at operation, and the study of serial radioisotopic liver scans suggest that liver regeneration in man is initiated very soon after partial hepatectomy and is well advanced within 10 days of operation.The remarkable regenerative capacity of the liver following major hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1972
1972
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Moreover, we found that the satisfactory outcome group had a high portal velocity on PODs 1 to 3 (more than twice the preoperative value), which then decreased gradually. This marked change might correspond to the period of rapid regeneration of the remnant liver identified in a previous study [21], which showed that liver regeneration was well advanced in humans within 10 days after right hepatectomy.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, we found that the satisfactory outcome group had a high portal velocity on PODs 1 to 3 (more than twice the preoperative value), which then decreased gradually. This marked change might correspond to the period of rapid regeneration of the remnant liver identified in a previous study [21], which showed that liver regeneration was well advanced in humans within 10 days after right hepatectomy.…”
Section: Discussionmentioning
confidence: 74%
“…[48] The observation that the majority of the regeneration process occurs within 10 days of resection in healthy patients was reported in 1971. [49,50] Fig. 5 provides an example of hepatic regeneration in a patient who underwent an extended right hepatic resection.…”
Section: Assessment Of Liver Function and Regenerative Capacitymentioning
confidence: 99%
“…Better techniques of resuscitation and surgery have undoubtedly improved the once very serious prognosis in this situation. Blumgart & Vajrabukka (1972) reviewed forty-four cases of closed injury of the abdomen requiring laparotomy. Thirty-five of these were due to motor vehicle accidents; twenty of the forty-four cases had liver injuries, and in eighteen of these there were associated injuries, particularly to the head chest and skeletal system.…”
Section: Liver and Biliary Systemmentioning
confidence: 99%
“…Blumgart, Leach & Karran (1971) have made some interesting observations on their five patients after right hepatic lobectomy, which effects an approximate 50%. resection of liver substance.…”
Section: Liver and Biliary Systemmentioning
confidence: 99%